Transformation of Production Techniques and Textile Materials Towards Sustainable Fashion - Rizka Sarah Heydarina Fathima Ahsan; Jibril Maulana; Galih Janggan Titian; Dina Aulia Mawardah; Aurelia Vika Anggun R (Proceeding of the International Conferences on Engineering Sciences, 2026)
This study aims to analyze the relationship between production techniques, selection of textile materials and the level of sustainable fashion implementation in MSMEs in the fashion sector in Indonesia. The method used in this study is a quantitative approach with an expplanatory descriptive design. Data was collected through a questionnaire distributed to MSME respondents in the fashion sector and collected 100 respondents. The variables tested in this study are knowledge of sustainable fashion, production techniques used by MSMEs and textile materials applied in production. Data analysis used validity, readiness, t-test and multiple linear regression tests. The results of the study show that production techniques have a significant influence on the level of sustainable fashion implementation, with a p-value of 0.041. Meanwhile, textile knowledge and materials did not show a significant influence on the implementation of sustainable fashion with a p-value of >0.05. The value of the determination coefficient (R2) for production techniques is very high at 0.95, which shows that production techniques are the most influential factor in the implementation of sustainable fashion in MSMEs in the fashion sector to prioritize the development of sustainable production techniques as the main step towards increasing sustainability in the fashion sector.